Pelatihan Cara Menghitung Persentase Zakat serta Problematikanya di SMA Unggulan BPPT Al Fattah Siman Sekaran Lamongan - Ilahin, Nur; Faizah, Niswatul (TAAWUN, 2022)
Zakat is one of the five pillars of faith where zakat is a matter that must be done for everyone who has converted, but in its implementation in the community, there are many who are still neglectful in the matter of zakat, because they still consider their property to be completely owned by them. even though Allah SWT in his word in the Qur’an several verses state, in the wealth of the rich there is the right of the poor, and if the rights of the poor are not removed, they eat up the rights of others. So with this description, we carry out community service at the BPPT Al Fattah Siman Superior High School, because it is to invite zakat from an early age with an understanding of how to present zakat. This activity was carried out with the initial pretest method, socialization with lectures and practice and closed with a posttest to see the results of this activity. And after this activity, it is hoped that it will raise awareness of zakat and know the percentage of zakat that is good and right.